The impact of long-term organic farming on soil-derived greenhouse gas emissions - Skinner, Colin; Gattinger, Andreas; Krauss, Maike; Krause, Hans-Martin; Mayer, Jochen; van der Heijden, Marcel G. A.; Mäder, Paul; Justus Liebig University Giessen (My University, 2019)
Agricultural practices contribute considerably to emissions of greenhouse gases. So far, knowledge on the impact of organic compared to non-organic farming on soil-derived nitrous oxide (N2O) and methane (CH4) emissions is limited. We investigated N2O and CH4 fluxes with manual chambers during 571 days in a grass-clover- silage maize - green manure cropping sequence in the long-term field trial "DOK" in Switzerland. We compared two organic farming systems - biodynamic (BIODYN) and bioorganic (BIOORG) - with two non-organic systems - solely mineral fertilisation (CONMIN) and mixed farming including farmyard manure (CONFYM) - all reflecting Swiss farming practices-together with an unfertilised control (NOFERT). We observed a 40.2% reduction of N2O emissions per hectare for organic compared to non-organic systems. In contrast to current knowledge, yield-scaled cumulated N2O emissions under silage maize were similar between organic and non-organic systems. Cumulated on area scale we recorded under silage maize a modest CH4 uptake for BIODYN and CONMIN and high CH4 emissions for CONFYM. We found that, in addition to N input, quality properties such as pH, soil organic carbon and microbial biomass significantly affected N2O emissions. This study showed that organic farming systems can be a viable measure contributing to greenhouse gas mitigation in the agricultural sector.
Keywords: ddc:630